A case of non-lacrimal immunoglobulin G4 (IgG4)-related orbital disease with mastitis. (2nd January 2016) - Farooq, Tahir Ali; Mudhar, Hardeep; Sandramouli, S.
ABSTRACT: IgG4-related orbital disease is a recognised cause for orbital inflammation. As its awareness increases and diagnostic accuracy improves there will be an increased number of cases being identified. This unique case demonstrates for the first time, with histological evidence, a case of a non-lacrimal IgG4-related orbital disease with concurrent IgG4-related mastitis. We describe a 47 year old who presented with a supraorbital swelling and mass. This was initially successfully treated with oral steroids and was later excised on recurrence. Immunohistochemical and blood serum analysis confirmed IgG4-related orbital disease. On systemic enquiry she was found to have a mass of the breast, which was shown to be IgG4-related mastitis. She is currently asymptomatic with no sign of recurrence and is under long-term surveillance. This case highlights the importance of systemic work up in patients presenting with orbital foci of IgG4 disease.